Wpływ Kształtu na Współczynnik Oporu przy Ruchu Brył Izometrycznych w Nieruchomym Lepkim Płynie - Góralski, A (Engineering Transactions, 1964)
The problem is analysed theoretically, it being shown that the influence of the shape of the body on the drag coefficient in laminar motion may be taken account of by means of the laminar coefficient of completion δ = dz/d0, where de is the representative diameter of the body and δ – the diameter of a sphere circumscribed on it. It is also shown that the influence of the shape of the body on the drag coefficient in turbulent motion may be taken into account by means of the turbulent coefficient of completion δ2= (δz/δf)2, where δf is the diameter of the circle of which the area is equivalent to the mean area of a normal projection of motion pf the body on a plane normal to the direction On the basis of the experiments of Pettyjohn and Christiansen is determined the corresponding quantitative relation enabling us to compute the drag coefficient for a known shape of the body. It is assumed that the characteristic dimension of the body is the representative diameter dz.An analysis of these results justifies the opinion that the laminar and turbulent scheme motion a correct manner the phenomena considered.